Studi Pengaruh Artificial Intelligence dan Teknologi Informasi Terhadap Minat Kerja Mahasiswa dengan Rekrutmen Digital Sebagai Mediator - Sahabuddin, Romansyah; Arif, Hery Maulana; Sari, Nabiilah Atiqah; Yuniarti, Iin; Syahrani, Aulia (Abadi Institute, 2024)
This research aims to find out how artificial intelligence and technology influence students' work interests by using intervening variables in the digital-based recruitment process. This research uses quantitative research with research data analysis which is multiple linear regression analysis with path analysis. With the aim of establishing whether a set of independent variables (exogenous) has a direct or indirect impact on the dependent variable, a path analysis model is used to evaluate the interaction pattern between variables (endogenous). The sampling method used in this research is non-probability sampling method with purposive sampling technique. Purposive sampling is a sample data collection technique that presents complete information data and uses certain considerations or criteria, namely 100 respondents. The results of this research prove that there is a positive direct influence between artificial intelligence and technology on students' work interest, as well as an indirect influence through digital-based recruitment process variables.